Industrial training report: Jabatan Sukarelawan Malaysia (RELA), Kementerian Dalam Negeri / Nur Hazeerah Mohd Nasrul Hakim - Mohd Nasrul Hakim, Nur Hazeerah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
This internship at Jabatan Sukarelawan Malaysia (RELA) gave student a thorough understanding of how the organization contributes to community services and national security. Throughout time there, student took on various responsibilities, such as helping with paperwork, assisting in organizing events, and working on projects focused on improving public safety. A highlight of the experience was collaborating with RELA volunteers during disaster relief efforts and community outreach initiatives. Student also attended workshops about safety procedures and managing volunteers, which helped student learn about the challenges the department faces. This internship improved skills in communication, teamwork, and problem-solving, while also deepening appreciation for the important role that volunteer organizations play in national development. Overall, this experience significantly expanded student view on volunteerism and its effects on society.